Taula de multiplicar del

6 i

6

2
1

2

1

1

1

1

6

6

1

1

1

2

1

1

1

2

6

6

2

1

1

1

2

1

2

1

2

1

6

1
6

6

4

1

1

3

18

1

1

1

2

3

1

2

1

2

18
42

1

2

3

18

1

1

1

36

1

2

24

1

2

2

12

1

2

4

1

1

= 24
1

1

6

1

2

1

6

1

2

30

1

1

=

6

1

6

5

6
5

4
6

1

2

2

12

1

1

=
2

2

24

=

6

6

6

4

x

6

36

3

18

18
5

30

3

18

18
6

36

= 36
4

4

24

4

24

2

12

=
4

4

=

6

2

6

7

6

9

=

12
7

42

= 42
9

54

= 54
6

6

6

36

1

6

=

6

1

6

2

6

2

=

6
2

=
2

12

12
2

12

8

48

=

6

8

6

9

x
6

24

=

x
6

6

6

x
6

6

4

3

x
6

6

= 30

6

6

6

4

= 30

x

6

=
4

6

42

=

x

6

1

5

x
6

6

24

6

x
6

6
12

3

6

6

7

=

6

x

6

4

=
4

6

24

=
6

6

x

6
6

4

x
6

1

4

x
6

4

=

x

6
6

7

x
6

24

= 24

6

6

6
18

7

x

6

7

6

x

6

4

=
4

6

6

6

18

1

2

6

6

48

4
6

x

6
24

4

x
6

6

=

x
x

54

= 36
4

x

6
9

6

6

6

=

6

6

6

1

8

1

x

6

1

=

x
6

30

=

x
6

5

4

3

6

6

6
1

7

6

6

2

=

x

6
1

7

6

6

6

1

6

x

6
1

3

x
6

6

1

6

x

6

1

= 48

x
6

24

= 24

6

6

2

8

6

6

6

1

6

x

6
1

4

x
6

1

6

6

6

4

=

x
6

6

1

3

x
6

1

=
3

x

6
2

9

x

6

1

=
9

6

6

60

=
5

5

x

6
1

4
6

6

10

= 60
6

6

6
2

4

x

6

1

6

x
6

6
1

10

x
6

6
1

6

= 48
9

9

=

54

Taula de multiplicar del

6 i

6

2
1

2

1

1

6

6
1

1

2

1

1

6

6
6

1

2

1

1

6

2

1

1

1

2

6
6
1

1

2

2

1

1

1

2

1

2

6

x

1

1

1

12

6

5

6

3

30

1

7

42

1

1

7

42

1

2

1

1

30

1

2

18

1

1

7

42

1

2

=
6

6

36

1

1

9

54

1

1

=
9

6

9

6

2

9

1

1

1

2

= 54
2

2

=

6

6

6

4

6

1

36

1

1

1

1

1

1

= 36
4

= 24
1

=

6

8

6

1

1

30

4

24

1

6

6
5

30

2

12

12
8

48

1

6

8

48

=
8

= 48
3

3

3

18

7

42

6

36

1

6

=
7

7

=
6

6

=
1

=

x

6

6
6

x

5

6

36

5

30

7

42

=
7

7

6

=
5

6

x

5

= 48

6

6

6

6

x

6
6

48

=
2

6

6

8

=

x

6

24

5

6

6

54

=

6

6

6
6

5

x

6

12

6

x

6

9

=
1

6

6

6

54

4

x

6

= 54

4

6

6

36

=

6

x
6

6

6

5

x

6

= 42

5

6

6

6

=

x

6

3

8

x

6

48

=
8

x

6
5

9

x

6

8

= 36

6

6

2

9

6

6

6
1

6

x

6

12

6

x

6

18

=

6

6

6

3

=
8

8

x
6

6
12

3

x
6

6

2

7

6

1

3

6

x

6

= 30
3

x

6

12

6

6

6

=

x
6

1

2

2

x
6

12

=

2

x

6

6

2

x
6

2

= 42

6

6

6
2

2

x

6
1

6

x

6

2

=
7

6

6

6
1

7

x

6

1

5

7

6

6

36

=

6

x
6

1

6

2

5

x
6

1

6

6

36

=

5

x

6

1

2

6

6

1

6

=

x

6
1

2

x

6
1

6

x
6

1

=
2

6

6

6
1

6

x

6

6

6

6

6

48

=

6

x

6
1

6

x
6

8

= 48

x

6

1

6

6

6

1

6

x

6

1

8

x
6

6
1

6

=

Taula de multiplicar del

6 i

6

2
1

1

1

2

6

6

x
6

6
1

2

1

1

1

1

6

1

2

1

2

6
6

1

1

1

2

1

1

1

1

1

1

1

2

8

60

1

1

60

1

36

1

2

10

1

2

8

1

2

6

1

2

6

9

54

1

2

8

48

1

1

1

6

1

2

1

6

1

1

1

6

1

2

=
1

1
2

2

12

1

2

10

60

1

1

=
10

6

6

6

5

36

1

2

= 36
5
6

30

1

2

5

30

1

2

=
5

x

54

7

42

3

18

7

42

1

=

6

6
7

42

= 42
5

5

30

= 30
6

3

6

7

3

=
7

18

18
7

42

6

36

=
6

= 36
2

2

2

12

10

60

=
10

= 60
6

9

6

3

9

54

= 54
3

3

18

2

12

=

6

2

6

1

6

1

=

x
6

6

7

x
6

6

= 30

6

x
6

9

= 42

x
6

6

5

1

6

6

6
6

6

x

6

=

7

x

6
2

6

6

6

18

=

x

6

=

3

6

6

3

=

3

x
6

6

1

7

x
6

24

= 54

6

6

6
6

7

x

6

=

6

x
6

4

=
9

x
6

6

36

3

x
6

6

48

3

6

6

42

=

6

x

6

60

4

x
6

7

= 42

x

6
6

4

x
6

1

6

6

6

6

10

1

6

6

=

x
x

10

1

x
6

2

7

x

6
1

=

x 10

6

1

48

8

6

6

6

9

x

6

1

8

9

6

6

30

6

x
6

6

= 36

x

6

5

6

6

6

= 48

6

6

1

= 60

x

6
2

8

6

6

6
1

6

6

6

1

= 36

x

6
1

10

x

6

1

6

6

6

6
1

6

x

6
1

6

6

6

24

=

x

6

4

=

10

6

6

2

=
10

x

6
1

8

x
6

1

= 30

x
6

6

1

8

6

6

2

6

x 10

6

1

5

x 10

6
2

6

6

6

36

= 24

x
6

6

=
4

x
6

6

1

6
6

6

1

6

x

6

1

6

12
1

=

6

6
1

=

6

6

Taula de multiplicar del

6 i

6

2
1

2

1

1

6

6
2

1

1

1

2

6

6

1

2

1

2

6
6

1

1

1

1

6
6
2

1

1

2

1

1

6

1

1

1

2

6

6

5

1

1

8

48

1

2

4

6

7

1

7

42

1

6

36

1

2

6

36

1

2

5

30

24

42

1

1

6

36

1

2

=
6

6
6

2

6

5

2

=
5

12

1

2

1

1

12
5

30

6

6

6

10

36

1

2

1

2

= 36
60

9

6
9

54

1

2

5

30

1

1

9

54

1

2

=
5

5

6

6

= 54

6

6

12

12
12

12
60

6

36

3

18

3

18

=
=
3

=
6

8

6

2

18
8

48

= 48
2

2

12

5

30

=

6

5

6

7

= 30
7

42

= 42
6

3

6

1

3

=
1
6

x

2

10

3

3

x
6

48

2

6

x
6

8

=

x

6

=
9

10

x
6

18

=

x
6

3

=

x

6

=

9
6

10

2

6

6

6
6

6

6

6

60

=
2

x

6

=

8

x

6

10

=

6

x
6

18

8

6

6

6

=

3

x 10

6

7

36

3

3

6

6

6

= 60

x
6

36

=
10

x

6

1

3

x
6

6

= 36

6

6

6

1

3

x

6
4

6

6

6

1

6

x

6

1

6

6

6

24

= 36

x
6

4

=
6

x
6

6
1

4
6

6

1

4

x

6

= 24
7

x

6

42

6

6

6

36

=

6

x
x

2

6

7

5

6

6

1

= 36

x

6

60

= 36

6

6

6

6

x 10
6

6

= 42

x
6

6
1

6

x

6
1

6

x
6

6
1

7

6

6

10

7

6

x

6

2

=

6

6

12

= 42

x
6

1

18
2

8

x
6

1

= 48

x

6

1

6

6

6

1

= 60

x

6
2

6

x
6

6

1

6

x
6

1

10

x

6

1

6

6

6

18

=

x

6
2

2

6

6

3

=

x
6

6

1

2

x
6

2

6

x

6

1

3

x
6

6
1

6

18

18
1

6

4

24

=
4

= 24

Taula de multiplicar del

6 i

6

2
1

1

1

1

6

6

x
6

6
1

2

1

2

1

2

6

6

6
2

1

1

1

2

6

1

2

1

1

6
1

2

6

2

1

1

6
1

1

2

1

1

6

4

6

4

x

2

1

1

1

1

18
18
5

1

54

1

2

24

1

1

9

54

1

2

1

1

3

6

1

6

5

3

=

2

6

1

2

30

1

2

18
1

=
5

1

6
5

6

7

6

4

6
7

42

1

1

1

2

= 42
4

= 24
6

9

6

1

9

1

2

1

2

= 54
1

1

5

30

1

2

8

48

1

1

1

1

=

6

8

6

4

4

4

=

24

6

3
9

6

2

4

24

18

10

60

3

18

9

54

6

10

= 54
2

=

12

12

10

60

= 60
4

4

4

24

1

6

=
1

=
6

5

6

9

6
5

30

= 30
9

54

= 54
6

10

6

5

10

60

= 60
5
6

x

6

=

6

x
6

1

3

3

x
6

12

= 60

x
6

2

=
10

x
6

6

3

6

6

48

= 24

x

6

= 48

3

x

6
5

6

6

6

6
6

=
5

6

6

54

4

x

6

24

6

x
6

18
8

=

x
6

6

=

1

x

6

18

=
1

6

6

18

=

2

6

6

18

3

2

x

6

18

8

x
6

3

=

x
6

6

36

8

6

6

6
6

6

x

6

4

3

x

6
9

6

6

6

18

=

x
6

3

=
3

x
6

1

3
6

6

6

30

3

x

6

18

= 36
6

x

6

18

=

x
6

1

= 54

x

6

36

6

6

6

3

6

6

6

3

9

6

6

2

= 54

x
6

6

9

x
6

6
1

6

x
6

1

=

x
6

6
1

5

x
6

18

6

5

x
6

3

=

x
6

1

=

6

6

6
2

3

x

6

1

6

6

6

1

= 36

x

6
2

3

x
6

6

1

6

x
6

2

6

6

6

42

=

6

x

6

1

3

x
6

7

=
3

x
6

6

1

7

x
6

1

7

6

x

6

1

6

30

9

54

=
9

9

5

=

Taula de multiplicar del

6 i

6

2
1

1

1

2

6

6

x
6

6
1

2

1

1

1

2

6

1

1

1

1

1

1

1

1

1

1

2

2

1

1

1

2

1

2

6
6

x

2

6

5

6

5

54

1

42

1

2

8

48

1

2

3

18

1

2

6

48

1

2

2

12

1

2

1

6

1

2

6
42

1

2

3

18

1

1

6
18
5

1

1

5

1

1

6

30

1

6

6

6

4

=

6

1

2

36

1

2

1

1

6
6

4

24

= 24

7

6

7

x

10

60

9

54

7

42

7

3

42

3

=
6

1

6

1

6

8

18

18
1

=

6

6
1

=

6

6
8

48

= 48
6

3

6

10

3

=

18

18

10

60

=
5

5

5

30

7

42

8

48

=
7

7

=

6

8

6

10

6

1

= 48

x
6

6

= 42

x

6

6

= 42

x
6

1

= 54

6

6

6

6

x

6

= 36

9

6

6

6
1

6

x 10
6

42

= 60

x
6

6

30

10

x
6

7

=

x
6

36

=

x
6

36

6

1

6

6

6
7

7

x

6

=

6

6

6

= 36

x

6
8

7

x
6

2

6

x
6

6
1

6

x

6

54

6

6

6

48

= 36

6

6

8

= 48

x

6

7

6

x
6

2

6

x
6

6

= 30
5

6

6

=

x
6

1

=
3

x
6

6

7

7

x
6

48

=

x
6

6
2

1
6

6

8

=
1

x

6
1

2

x

6

1

=
2

6

6

1

8

x

6

12

=

8
6

6

2

2

9

8

6

x

6

1

9

x

6

1

=
9

6

6

48

6

x
6

6

=
3

3

x

6
1

8

6

6

=
8

6

6

2

9

7

7

x

6

1

=

9

6

6

42

= 54

x

6

7

8

8

6

6

2

= 48

x

6

1

2

x
6

1

= 48

6

6

6

1

2

6

6

1

6

x

6

1

8

x

6
1

6

6

6

18

= 42

x
6

3

=
7

x
6

6

1

3
6

6

2

3

x

6

1

6

10

60

= 60
1

1

=

6

Taula de multiplicar del

6 i

6

2
1

2

1

1

6

6
1

1

1

1

2

6

1

1

1

1

1

2

1

1

1

1

6
6
2

1

1

1

1

2

6

1

1

1

1

6

7

6

7

7

1

2

54

1

30

1

1

10

60

1

2

2

5

30

2

10

60

1

2

42

1

1

42

1

7

42

1

2

1

1

5

30

1

2

=
5

3

6

7

3

=
7

1

1

18
42

1

2

9

54

1

2

=

6

6

10

6

1

1
3

6

6
42

6

36

10

60

1

6

3

18

1

6

=
1

=
8

8

6
8

48

9

54

=
9

= 54

x

9

9

9

54

8

48

=

6

8

6

7

x
x

1

7

3

6

6

48

=

x

6

8

= 60

6

6

48

= 36

6

6

6

6

x

6

7

=
9

9

18

18

=

x

6

18

8

7

6

6

36

= 42

x

6

6

3

1

6

6

6

= 30
6

6

12

=

x

6
36

8

x
6

2

= 48

x
6

6

6

8

6

6

6

1

6

x

6
7

8

x

6
7

6

6

6

42

=

x

6
1

3

x
6

7

= 36
6

6

24

=
6

x

6
1

2
6

6

4

=
2

x

6
42

7

x

6

7

7

6

6

30

= 24

x
6

5

=
4

6

6

6

5

5
6

6

2

5

x

6

=

6

x

6

2

6

6

x

42

= 42

x
6

7

6

6

6

=

x

6

1

=

7

6

6

1

1

7

x

6

42

= 30

x
6

6

10

6

6

6
2

6

x

6
1

5

x
6

6
1

6

x

6

7

= 42

6

6

1

54

7

x 10
6

1

=

x
6

18

=
10

x

6

1

5
6

6

3

=

x 10

6

6

9

5

6

6

2

6

6

9

9

9

x

6
2

9

6

6

1

= 54

x

6

24

= 42

6

6

1

=
7

x

6

1

7

6

6

1

=
7

x

6

4

3

6

6

54

=

3

x

6

1

4
6

6

9

= 54

x

6

1

4

6

6

2

6

x

6

1

9

x
6

6
1

6

= 48
7

42

= 42

Taula de multiplicar del

6 i

6

2
1

2

1

1

6

6
1

1

2

1

2

6

6
6

1

2

1

2

6
1

2

1

2

1

2

6

6
6
2

1

1

6

6
2

1

1

6

1

1

1

2

8

6

6

7

2

1

1

6

6

2

6

8

1

1

10

3

1

54

1

1

8

1

2

7

1

2

2

1

1

36

1

1

2

1

1

=

1

1

12
8

= 48
1

6

1

1

=
1

1

2

6

1

2

6

=

6

7

6

7

42

1

2

1

1

= 42
7

42

2

12

1

2

2

12

1

2

7

42

1

1

=
2

2

6

= 42

6

2

2

54

3

18

18
60

9

54

2

12

4

24

9

54

5

30

=
4

4

=
9

9

=

6

5

6

3

= 30
3

=
6

3

6

8

8

18

18
3

=

18

18
8

48

6

36

=

6

6

6

1

6

10

= 36

x
6

9

=

x
6

54

10

9

9

x
6

9

= 60

x
6

6

=
7

6

12

=

x

6
2

10

x
6

6

=

2
6

7

6

6

6

2

=
3

x

6
7

9

x

6

1

9

6

6

6
6

9

6

x

6

48

18

=

6

6

3

= 54

x

6

12

2

6

6

36

=

x
6

30

6

2

x

6
6

3

x
6

5

= 36

6

6

6

12

3

6

6

6

42

6

x

6

48

6

x

6
9

6

6

6

18

= 30

x
6

3

=
5

x
6

2

3
6

6

6

18

3

x

6

60

= 36

6

x

6

=

6

x
x

60

2

6

6

10

= 42

x

6

2

= 48

6

6

1

= 54

x
6

6

6

x
6

6
1

9

x

6
1

6

x
6

36

6

6

6

=

x

6

1

3

x
6

2

6

3

x
6

1

6

6

36

= 60

6

6

1

= 60

x

6

1

10

x

6
1

6

x
6

1

=
10

x
6

6
1

6
6

x

6

6

6

6

6

48

=

x

6
2

6

x
6

8

= 48

x

6

1

6

6

6

1

6

x

6

1

8

x
6

6
1

6

1

=

x 10

10

=

6

6
60

Taula de multiplicar del

6 i

6

2
1

2

1

1

6

6
2

1

2

1

2

6

6

6
1

1

2

1

2

6

1

2

1

2

1

6
6
1

2

1

2

6

6
1

1

1

1

2

1

6

10

10

6

9

1

12
3

18

1

6

5

6

4

9

54

1

2

6

36

1

1

1

1

6

10

1

1

10

1

2

60

1

2

9

1

2

54

5

30

4

24

1

2

6

=

6

3

6

6

=

18

1

1

1

1

18
6

36

4

4

1

1

5

30

1

1

3

18

1

2

=
5

5
6

24

=

18

6

4

6

5

36

6

36

4

24

3

18

4

24

6

10

= 24
5

30

= 30
10

60

= 60
6

6

6

36

1

6

=
1

=
4

4

3

x

24

5

30

3

18

1

6

3

18

=
1

1
6

4

=
3

6

6

=
5

5

x

x

6

=

6

6

6

60

=

3

x

6

10

3

6

6

42

=

4

x
6

18
7

4

6

6

6

=
3

6

6

6

18

= 36

x

6

4

6

x

6

= 36

6

6

6

6
3

6

x
6

3

=

x
6

6
1

10

x
6

24

=

6

x

6
1

7

6

6

4

=

6

6

6

10

7

x

6

60

6

x
6

60

=
3

x

6
60

4

x 10
6

10

4

6

6

42

=

6

x
6

7

= 42

x
6

6
6

10

x

6
1

6

6

6

6

= 30
4

6

1

7

x 10

6

= 54

x
x

1

6

x
6

6

12

= 60

6

6

2

=

6

x

6

1

= 60
10

6

6

18

18

=

6

6

1

= 36

x
6

6

6

x
6

1

=
6

x

6
1

9
6

x
6

1

12
2

9

x
6

1

=

x

6
1

3

12

3

3

x 10
6

2

6

60

2

=

6

6

1

6

=

6

6

6
2

2

x

6

1

6

x
6

10

=

x
6

6

1

3

x

6

1

6

6

6

2

2

x

6

1

6

6

6

30

=

x
6

5

= 30

x
6

6

1

10

x
6

1

6

x 10

6

1

5

x
6

6
1

6

=
3

=

18

Taula de multiplicar del

6 i

6

2
1

1

1

1

6

6
2

1

2

1

2

6

6
1

6
2

1

1

1

2

6

1

1

1

2

1

1

2

6

1

2

1

2

3

1

1

1

18

1

2

18
1

1

1

6

1

1

6
1

1

12
3

18

1

2

1

6

1

2

6

36

1

1

=

1
6

8

6

1

8

1

1

1

1

= 48
1

1

=
10

60

1

1

24

1

1

=
= 24
7

7

7

42

1

2

3

18

1

1

1

1

=

6

3

6

8

18
8

48

= 48

6

2

2

60

3

18

18
2

12

4

24

6

36

9

54

1

6

10

60

=
6

6

=
9

9

=
1

1

=

6

10

6

3

= 60
3
6

x

10

4

4

x
6

24

=

x

6

4

=

6

6

48

= 60

6

6

6

3

x

6

=

6

x

6

8

=
10

6

6

54

=

6

x

6
4

9

=

4

x

6

24

6

4

6

6

6

10

4

6

4

1

8

8

x

6
6

1

x
6

60

= 54

x
6

6

48

1

6

6

6

= 36

6

x

6

=
6

9

x

6

10

=

6

6

6

60

4

4

x

6
12

6

6

10

=

x

6

30

=

10

x 10

6

5

=
10

6

6

6

=

5

x

1

=

x 10

6

6

5

6

6

1

1

1

x

6

36

1
6

6

1

6

2

1

x
x

1

6

60

3

3

6

6

1

6

6

=

x

6

1

1

6

x

6

42

10

2

x

6

30

7

=

6

6

1

=

x

6

48

5

1

x 10
6

6

6

6

6

8

6

6

6

=

x

6
1

6

x

6
1

6

x

6
1

3

6

6

1

=

6

x

6

1

10

6

6

1

= 42

x
6

18

6

6
3

= 30

6

6

6
1

7

x

6
2

6

6

6

1

= 48

6

6

6

1

5

x

6
1

6

x
6

6

1

8

x
6

2

6

6

6

1

=

x 10

6

1

3

x
6

60

=

x
6

10

3

x
6

6

1

6

x

6

1

10

x 10
6

6
1

6

18

8

48

=
8

8

3

=